É possível aplicar o adicional de 25% para todas as aposentadorias do RGPS? - Gurgel, Jeritza Pompeu Andrade (2016)
The additional 25% (twenty-five percent) provided for in article 45 of Law nº 8.213 / 91 is a benefit provided by the social assistance to retirees due to disability who prove that they need permanent help from third parties. Because it is a welfare benefit, it must be provided to all who need it without prior contribution, which, it is emphasized, is not confused with the precedence of the source of cost, a requirement not required for the granting of the said additional to the Retired due to disability, but often used to justify decisions denying the extension of the additional to the other retirement modalities of the RGPS. Due to a legislative misconception, there is no legal provision for granting this benefit to other retirees, other than those due to disability. This has led to a deadlock in jurisprudence and a consequent disrespect for the principles of isonomy and human dignity, which demonstrates the need for a serious analysis, capable of substantiating a change in the application of this norm, either through the uniqueness of jurisprudential understandings or through Legislative innovation. However, for the case here, the simple application of an analogical interpretation of the norm would solve the demand in the short term, which is necessary, in view of the fact that this is a fundamental provision to increase the possibilities of access to health And, consequently, guarantee respect for human dignity.